Activated Surface Charge‐Reversal Manganese Oxide Nanocubes with High Surface‐to‐Volume Ratio for Accurate Magnetic Resonance Tumor Imaging. (16th June 2017) - Lei, Ming; Fu, Chen; Cheng, Xiao; Fu, Bin; Wu, Niuniu; Zhang, Qiang; Fu, Ailing; Cheng, Jingliang; Gao, Jinhao; Zhao, Zhenghuan
Abstract : Investigating the surface structure, including crystal surface and surface‐coating ligands, of nanoparticulate T 1 contrast agent may help to understand the T 1 relaxation enhancement in vitro and in vivo. This study presents a novel strategy to develop high‐performance T 1 magnetic resonance imaging (MRI) contrast agents through optimizing the nanocrystal surface and the nanobio interface. Based on the optimized crystal surface, the novel manganese oxide nanocubes (MOCs) show significantly higher surface‐to‐volume ratio and an approximately threefold higher r 1 value compared to traditional manganese oxide nanospheres. Concurrently, transferring MOCs into aqueous media by dopamine derivatization can avoid the oxidation of Mn(II) ions and provide abundant magnetic core. This optimized surface endows MOCs with a high chemical exchange efficiency during T 1 relaxation. Of particular significance, a rationally designed pH‐induced charge‐switchable surfaces can be negatively charged and corona‐free in blood and positively charged surface in tumor sites. This unique feature improves the circulation behavior of this intelligent T 1 contrast agent in blood and increases cancer cell uptake to achieve accurate detection of solid tumor, holding great potential in aiding early and precise tumor diagnosis. This study provides a novel tool for sophisticated design of high‐performance T 1 MRI contrast agents in bioimaging applications. Abstract : Surfaces of biomedical nanomaterials can be mainly divided into two aspects, those are crystal surface and nanobio interface. Chemical exchange between surface of T 1 contrast agents (CAs) and protons is the key factor to shorten longitudinal relaxation of protons. Thus, one can develop superior T 1 CAs by engineering the crystal surface and nanobio interface to access accurate diagnosis.